Biochar modification enhances mechanical and durability properties of cement-based materials - Fufei Wu; Qiuyue Zhang; Shuangkuai Dong; Yang Cai; Shan Yang; Fajun Xu; Pengfei Luo; Jixiang Jiang (Scientific Reports)
Abstract In light of the existing carbon imbalance and environmental risks linked to cement manufacturing, diverse forms of biochar materials have been integrated into cement composites. This approach presents a mutually beneficial solution, effectively mitigating CO2 emissions while concurrently yielding economic benefits. This paper focused on replacing 0.1–24% of cement with apricot shells, along with biochar from palm, date, and peach shells at an 8% replacement rate. A nearly linear decline in workability and density was observed in biochar-mortar admixtures, as indicated by the results. With the addition of 1% biochar, the UHPC matrix achieved a peak compressive strength, surpassing that of the control by 2.65%, subsequent increments weakened it. Biochar-added UHPC mortars exhibited a diminished drying shrinkage, and the improvement in anti-permeability was confined to biochar additions ranging from 0.1 to 2%. Inclusion of 0.1–1% biochar in UHPC mortars reduced electrical flux, attributed to their “micro densification” effect. With 1% biochar substitution for cement, MIP analysis disclosed minimal porosity, complemented by SEM imagery showcasing abundant hydration products, underscoring the superior modification achieved in UHPC mortar. Deployed as an additive in UHPC mortar, biochar demonstrates potential success, fostering waste recycling while sequestering carbon within building materials.